The Analysis of Motivation Factors in Application on Linear Induction Electric Drives - Poška, A.; Rinkevičienė, R.; Savickienė, Z. (Elektronika ir Elektrotechnika, 2006)
The article deals with the factors of application of linear induction motors from the point of view of system engineering: the factor of equipment construction simplification, factor of application of LIM features in elaborated flexible production systems, the factor of possibility to apply of non-traditional control and regulation methods, the factor of LIM secondary element catapulting and levitation, factor of modular system designing, factor of control system simplification considering the LIM specific features, fast-operation factor, factor of multifunctionality, factor of movement transfer to closed space determined the successful development of real and exploited systems with LIM. The examples of developed automatic systems are presented; the principles of their performance are analyzed. Ill. 3, bibl. 8 (in English; summaries in, English, Russian and Lithuanian).